Microwave-Assisted Synthesis, Lipophilicity and In Vitro Antimicrobial Activity of Hydrazide-Hydrazones of Phenylacetic Acid - Magda Kuć; Anna Berecka-Rycerz; Anna Biernasiuk; Łukasz Popiołek (Applied Sciences)
Microwave-assisted synthesis was applied to obtain fifteen hydrazide-hydrazones of phenylacetic acid. The chemical structure of the synthesized compounds was confirmed on the basis of the analysis of the IR, 1H NMR and 13C NMR spectra. Experimental logP values for all obtained acylhydrazones were established with the use of chromatographic methods. The synthesized compounds were tested for potential antimicrobial activity in in vitro conditions against a panel of microorganisms, which included eight strains of Gram-positive bacteria and six strains of Gram-negative bacteria as well as six strains of yeasts belonging to Candida spp. The assays we performed revealed significant antibacterial activity of obtained hydrazide-hydrazones of phenylacetic acid. Some of the tested compounds possessed much higher activity than that of reference antimicrobial agents towards Gram-positive bacterial strains. It is also worth mentioning that some of synthesized compounds possessed significant activity towards MRSA strain—methicillin-resistant Staphylococcus aureus ATCC 43300 and MSSA strain—methicillin susceptible Staphylococcus aureus ATCC 6538 and ATCC 29213.